EuReCa_Serbia 2014-2023 Time from call to arrival at the scene of the accident - impact on the initiation of CPR measures - Lazic, Aleksandra; Vasilic, Milica; Medic, Sara (Journal Resuscitatio Balcanica, 2024)
Introduction: The rate of non-initiation of cardiopulmonary resuscitation (CPR) in patients with out-of-hospital cardiac arrest (OHCA) varies widely across countries, with limited findings in the literature addressing factors associated with higher rates of non-initiation, particularly reaction time (RT) of the emergency medical service team. The aim of this study is to analyze the data on RV length in relation to the initiation or non-initiation of CPR, including the collapse location, OHCA etiology, and the patient ageas additional factors potentially related to the frequency of CPR non-initiation. Material and Methods: In this study, data on initiation and non-initiation of CPR measures, length of RV, collapse location, OHCA etiology, and age of patients were collected and analzyedaccording to the protocol of the EuReCa study during the period October 1, 2014 - December 31, 2023. Results: A total of 10458 EuReCa events with a median RV of 9 (IQR 5-17) minutes were recorded during the follow-up period. In 6197/10458 cases (59.3%) CPR measures were not initiated. Statistically significantly longer RV was observed in the group of patients in whom CPR measures were not initiated, compared to cases where those were applied (Med = 25 (IQR 10-45) vs. Med = 6 (IQR 4-10) minutes, respectively); p<0.001). In relation to the location, both in the group with initiated and non-initiated CPR, a statistically shorter RV was observed when it occurred in a public place compared to the patient’s residence (p<0.001), as well as when compared to other collapse locations (p<0.001). In terms of etiology, a significantly shorter RV was observed in the group where CPR measures were not initiated, when comparing the groups of patients with traumatic OHCA compared to cardiac OHCA (p<0.001) and traumatic OHCA compared to OHCA of other causes (p=0.001). Among individual age categories, significant differences in RV duration were observed in the group of patients where CPR measures were not initiated (H=83.553; p<0.001), but also in the group of patients where the same were initiated (H=21.260; p=0.012). Conclusion: The reaction time of the emergency medical service team is significantly longer in cases where CPR is not administered. Public place as the collapse location, certain etiological factors, and certain groups of patient age were significantly associated with shorter RV, which may indicate the presence of relation of potential factors that may contribute to it’s prolongation in cases where CPR is not applied. Additional analyzes are necessary to determine the cause-and-effect relationship between RV length and the frequency of initiation and non-initiation of CPR measures, as well as the influence of other potential factors with the aim of increasing the chance of survival after OHCA.